Stakeholders decision-making criteria for adaptive reuse strategy: Malacca and Penang heritage cities / Noorzalifah Mohamed - Mohamed, Noorzalifah (2017)
Adaptive reuse is an important strategy for achieving sustainability, as it ensures a continuous building life cycle and prevents building destruction. Adaptive reuse has the greatest potential to significantly decrease the environmental load of the built environment within the next 20 to 30 years. However, owners and practitioners still lack of point of references to justify and evaluate their decision-making with regard to the adaptation practice. The decision to reuse a building entails a complex set of considerations, including issues of economic, social, environmental, legislative and architectural. This research, therefore, aims to explore the unique criteria of decisionmaking among practitioners when considering to adaptive reuse an existing building asset. Thirty (30) unique criteria of decision-making were identified through detailed literature review. The quantitative method of a self-completion questionnaire survey were conducted among stakeholders, including architects, valuers, planners, government department, developers and the building owners gather their opinion and view on criteria that influence the decision-making. The analysis of the survey revealed seven (7) key criteria that are influencing the decision-making to adaptive reuse the existing building: (1) building value; (2) building suitability; (3) structural condition; (4) official plan and zoning; (5) building code; (6) client requirement and (7) heritage designated. In this regard, while 'building value' criteria were the primary determinants influencing the decision to reuse or demolish, the suitability and structural condition of the asset juxtaposed with regulations were also considered. Additionally, issues associated with the environmental, economic and social tenets of sustainability were identified as being important, but were given less priority when considering reuse. As current building stock is rapidly becoming obsolete, emphasis is increasingly placed on them during the adaptive reuse decision-making process to ensure sustainable outcomes. The developed criteria identify the critical areas that owners, developers and key project stakeholders need to consider when deciding to either reuse or demolish an existing building. It also can be used to evaluate the economic, physical and social implications of undertaking a heritage project